ANALISIS PENGARUH ATRIBUT PRODUK WISATA TERHADAP KEPUTUSAN WISATAWAN BERKUNJUNG (STUDI PADA DAERAH WISATA PULAU LOMBOK) - DETHAN, STEVANY HANALYNA; MEIKAPASA, NI WAYAN PUTU; CATHARINA, THERESIA SUZANNA (GANEC SWARA, 2020)
The purpose of this research is to analyze the effect of product attributes on the decision of visiting tourists (a study in the tourist area of Lombok Island). This type of research is associative research. Sampling was carried out using non-probability sampling, namely the incidental sampling technique of 75 respondents. Data were analyzed by multiple linear regression. The results of this study indicate that partially and simultaneously the product attributes (attractions, amenities and accessibility) have a significant effect on the decision of tourists to visit the tourist areas of Lombok Island